Hadis Dan Sunnah Nabi Dalam Perspektif Joseph Schacht - Anwar, Latifah (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2020)
Research about Hadith authenticity becomes Orientalist’s preferred study. Joseph Schacht, one of orientalist researcher had researched and criticized Hadith authenticity. Schacht assumed that Sunnah was not formerly from Prophet Muhammad, but it was the continuity of Arabian traditions which were revised and done continuously by Moslem and hold up to Prophet Muhammad. Schacht assumed that Prophet’s sunnah had not been established surely to Hadith. Schacht’s research was started by studying Islam law establishment process. Then, he concluded that Islam law had not been existed until Al-Sya’bi era (110H). At Tabi’in era, there was Hadith which was not available at the previous one. Hadith in Tabi’in’s era was considered complete than companions’ version. Hadith at the next version was spread out by falsification. Schacht mentioned that Isnad was part of arbitrariness in Prophet Muhammad Hadith since it was developed by different groups who expected to relate it to the previous one. Sanad reconstruction formation based on Schacht’s opinion, namely by doing backward design, known as Projecting Back theory. Sanad Hadith common indicators showed that the longer period of people far from Prophet Muhammad era, the more people narrated Hadith. Schacht mentioned that the practice of sanad Hadith was started from the simple way, then it was developed and formed the perfect sanad at the second period of third century of Hijriyah.